Pipoxolan inhibits CL1–5 lung cancer cells migration and invasion through inhibition of MMP-9 and MMP-2. (5th July 2015) - Lee, Min-Min; Chen, Ying-Yi; Liu, Pei-Yi; Hsu, Stephen; Sheu, Ming-Jyh
Graphical abstract: Highlights: Lower doses of pipoxolan markedly suppressed CL1–5 cells migration and invasion. Lower doses of pipoxolan significantly inhibits CL1–5 cell proliferation rate. These were associated with reduction activities and levels of MMP-2 and -9 in CL1–5 cells. Lower doses of pipoxolan significantly inhibited phosphorylations c-Jun N-terminal kinase, and p38 MAP Kinase of CL1–5 cells. Our conclusions show that pipoxolan down-regulates phosphorylation JNK and p38, and then, MMP-2 and -9 in CL1–5 cells. Abstract: Pipoxolan has been reported to have antitumor activity. However, the effects of pipoxolan on lung cancer cell metastasis remains unclear. This study examined the anti-metastatic effects of pipoxolan on lung adenocarcinoma cancer cells ( i.e. CL1–5, CL1–0, and A549) and its underlying molecular mechanisms. Firstly, CL1–5 cell migration was markedly suppressed by pipoxolan when examined by wound scratch assay. Furthermore, transwell and matrigel invasion assays revealed that pipoxolan inhibited lung cancer cells ( i.e. CL1–5, CL1–0, and A549) migration/invasion, and showed more sensitive to CL1–5 cell. Therefore, the anti-metastatic effects from pipoxolan have been focused on CL1–5 lung cancer cells. Secondly, these observations have been associated with the reduction in the activities and expressions of matrix metalloproteinase (MMP)-2 and -9 in CL1–5 lung cancer cells. Lastly, pipoxolan administration significantly inhibited phosphorylation c-Jun N-terminal kinase (p-JNK), and p38 MAP Kinase (MAPK) of CL1–5 cells. Based on these results, our results showed that management CL1–5 cells with pipoxolan down-regulated phosphorylation JNK and p38, and then, MMP-2 and -9. These results suggest that pipoxolan might have a new therapeutic potential for anti-metastatic effects in lung cancer cells.